Application of Raman spectroscopy in the identification of oral bacteria - QI Linlong, QIN Zirui, TENG Jianying, ZHANG Shuyang, WANG Yuan, DENG Shuli (Editorial Office of Stomatology, 2024)
Oral bacteria are associated with a variety of oral diseases such as caries, periodontal disease and oral cancer. Some pathogenic bacteria also play an important role in the occurrence and development of systemic diseases. The rapid identification of bacterial pathogens helps the diagnosis and precise treatment of oral diseases. Raman spectroscopy is a simple, rapid and non-invasive novel detection technique that can provide abundant and detailed bacterial information and can rapidly identify bacteria, but the application of this technique in oral clinical settings is still relatively rare and needs further exploration. This paper summarizes the research progress of Raman spectroscopy in the identification of oral bacteria and discusses the prospects and challenges of its clinical application.